Effect of magnification on root coverage surgery - Marcella Goetz Moro; Maria Luisa Silveira Souto; Emanuel Silva Rovai; João Batista Cesar Neto; Marinella Holzhausen; Claudio Mendes Pannuti (Universidade Estadual de Campinas, 2020)
Root coverage surgery can be performed in patients with gingival recession to cover the exposed root aiming to control hypersensitivity and promotes better aesthetic. Optical magnification has been proposed as a refinement in this surgical technique to increase root coverage. This approach may lead to enhanced soft tissue stability, less post-operative discomfort, better predictability and esthetic appearance. Aim: This systematic review aimed to evaluate the effectiveness of magnification on root coverage surgery when compared to procedures performed without magnification. Methods: Randomized controlled trials with a follow-up of at least 6 months that compared surgeries for root coverage performed under optic magnification versus conventional (macro) root coverage surgery were screened. The primary outcome was mean root coverage (mm) (MRC) and secondary outcomes were percentage of root coverage (PRC) and complete root coverage (CRC). Results: Of 569 papers relevant to this review, seven were included. Meta-analysis showed that the use of magnification may favor greater PRC (7.38%, 95% CI 3.66-11.09). Conclusion: Magnification can increase PRC in root coverage surgeries. More randomized trials with the use of magnification may be necessary to verify if this benefit is clinically relevant, in order to justify the use of this device.